PASSIVE ANALYSIS ON JAVANESE DIALECT IN PURWOBAKTI VILLAGE BUNGO REGENCY PROVINCE OF JAMBI - Asridayani, Asridayani; Suryani, Ratri (Universitas PGRI Sumatera Barat, 2020)
This study is the result of research about the description of passive analysis on Javanese dialect in Purwobakti Village Bungo Regency Province of Jambi. The purpose of this reseacrh is to explain the forms of passive marker that used in Javanese dialect especially uttered by community in Purwobakti village Bungo Regency Province of Jambi as an object and subject of the utterance. The researcher uses qualitative reseacrh method to do the research. Whereas, to analyze the data, the researcher uses the theory from Wedhawati, et al(2006) about the passive verb and passive markers. The data are found by recorded the conversation of Purwobakti villagers. Then, the researcher uses formal and informal method in presenting the data. As the result, there are two classifications of passive markers uttered by people in Purwobakti village Bungo Regency, Province of Jambi, Indonesia. Firstly, Passive voice with the first person as object is marked by an affixes tak, tak-i, tak-(a), tak-ne, and tak-ane. The last, passive voice with the third person as object of the sentence marked by affixes di-, di-i, and di-(a)ke. Therefore, the passive markers influence the object of sentences and the construction of sentence.